Policy and persistence of stock returns volatility: conventional versus Islamic stock market / Rosylin Mohd. Yusof and M. Shabri Abd. Majid (Faculty of Business and Management ; UiTM Press, 2006)
This paper examines the extent to which the conditional volatilities of both conventional and Islamic stock markets in a small developing stock market, Malaysia, are related to the conditional volatility of monetary policy variables. Among the monetary policy variables tested in the study are money supply Ml and M2, interest rates (TBR), exchange rate (MYR), and Industrial Production Index (IPI), while the Kuala Lumpur Composite Index (KLCI) and Rashid Hussain Berhad Islamic Index (RHBII) are used as measures for conventional and Islamic stock markets, respectively. In order to capture the international influence on both stock markets, the volatility in the US monetary policy variable measured by the Federal Funds Rate (FFR) is incorporated into the study. The Autoregressive Conditional Heteroskedasticity (ARCH) and Generalized Autoregressive Conditional Heteroskedasticity (G ARCH) frameworks are employed for the monthly data starting from January 1992 to December Z000. The study finds that the growth rates of TBR or interest rate has a predictive power in explaining the volatility in the conventional stock market, while for the Islamic stock market TBR is found to be an insignificant variable. This highlights the tenet of Islamic principles that the interest rate is not a significant variable in explaining stock market volatility. Therefore, the importance of stabilities in these variables should be noted in designing policies to stabilize both conventional and Islamic stock markets.